(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A thinly populated rural community with a concentration on agricultural occupations. Rural lifeis characterised by a simple culture, a natural environment, and an informal social life. Such individualsare frequently homogeneous in their vocations, clothing, language, and social practises. Because of thesluggish speed of communication, the rate of change is slow. Their occupation is agriculture. In paper Idiscuss the history of rural society, problems in rural development, analysis and general solutions ofproblems in rural development, socio-economic status of rural women, labour force participation ofwomen, factors imposing detrimental effects upon status of women, measures to enhance the status ofrural women.